Bond between TRM versus FRP composites and concrete at high temperatures - Raoof, Saad M.; Bournas, Dionysios A. (Elsevier, 2017)
The use of fibre reinforced polymers (FRP) as a means of external reinforcement for strengthening the existing reinforced concrete (RC) structures nowadays is the most common technique. However, the use of epoxy resins limits the effectiveness of FRP technique, and therefore, unless protective (thermal insulation) systems are provided, the bond capacity at the FRP-concrete interface will be extremely low above the glass transition temperature (Tg). To address problems associated with epoxies and to provide cost-effectiveness and durability of the strengthening intervention, a new composite cement- based material, namely textile-reinforced mortar (TRM) has been developed the last decade. This paper for the first time examines the bond performance between the TRM and concrete interfaces at high temperatures and, also compares for the first time the bond of both FRP and TRM systems to concrete at ambient and high temperatures. The key parameters investigated include: (a) the matrix used to impregnate the fibres, namely resin or mortar, resulting in two strengthening systems (TRM or FRP), (b) the level of high temperature to which the specimens are exposed (20, 50, 75, 100, and 150 °C) for FRP-reinforced specimens, and (20, 50, 75, 100, 150, 200, 300, 400, and 500 °C) for TRM-strengthened specimens, (c) the number of FRP/TRM layers (3 and 4), and (d) the loading conditions (steady state and transient conditions). A total of 68 specimens (56 specimens tested in steady state condition, and 12 specimens tested in transient condition) were constructed, strengthened and tested under double- lap direct shear. The result showed that overall TRM exhibited excellent performance at high temperature. In steady state tests, TRM specimens maintained an average of 85% of their ambient bond strength up to 400 °C, whereas the corresponding value for FRP specimens was only 17% at 150 °C. In transient test condition, TRM also outperformed over FRP in terms of both the time they maintained the applied load and the temperature reached before failure.